Effectiveness of Android-Based Waterwheel Teaching Aid to Improve Students' Critical Thinking Skills - Nisrina Najikhah; Raden Wakhid Akhdinirwanto; Ashari Ashari; Nasrun Balulu (Radiasi : Jurnal Berkala Pendidikan Fisika, 2022)
A study has been carried out on android-based waterwheel props used for dynamic fluid learning. The aim is to increase skills of critical thinking of students. The research subjects were 22 students of the sixth semester of Physics Education Study Program, Faculty of Teacher Training and Education, Muhammadiyah University of Purworejo. The implementation of the research is: before learning students are given a pretest of skills of critical thinking, then learning is carried out using an android-based waterwheel prop, then given a posttest with questions that weigh the same as the pretest questions. Furthermore, n-gain was calculated from the pretest-posttest tests of critical thinking skills, and analyzed by parametric and/or non-parametric analysis of statistical. The results of this study is a significant increase in skills of critical thinking at the 5% significance level with an average n-gain greater than 0.7 which means in the high category, and the Anova test produces a Sig score. of 0.342 which means it is greater than the probability score of 0.05 so that Anova test results show that there are similarities in the improvement of skills of critical thinking in the two learning meetings.